Financial education, literacy and investment attitudes - Agar Brugiavini; Danilo Cavapozzi; Mario Padula; Yuri Pettinicchi (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
Based on a sample of university students, we provide field and laboratory evidence that a small scale training intervention has both a statistically and economically significant effect on subjective and objective assessments of financial knowledge. We show also that the intervention increases self-assessed more than actual financial knowledge.
Keywords: D14; G11; I20; 330; Financial education; Financial literacy; Planning; Investment attitudes